Studi Kualitatif Gangguan Pendengaran Akibat Bising di Bengkel Bubut X Sidoarjo - Nafia, Zidni Ilman; Rhomadhoni, Muslikha; Saputra, Naufal; Ratriwardhani, Ratna (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Noise is one of the most dangerous factors in the workplace. Noise can lead to hearing impairment and the risk of temporary or permanent damage to the sense of hearing after exposure for a certain period of time without the use of adequate protective equipment. The aim of the study is to find out the picture of hearing impairment due to noise experienced by workers X Sidoarjo. This study uses a qualitative descriptive approach with observational methods. The result of this study was that 2 out of 10 informants suffered from hearing impairment. The main source of noise in the powder workshop X Sidoarjo is the powdering machines and tooling and scrubbing. Prevention can be done through the use of ear protectors against workers and the implementation of socialization of safety and health at work in order to create a safe and secure workplace environment.